2020
DOI: 10.1016/j.jacbts.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter-Delivered Expandable Bioresorbable Polymeric Graft With Stenting Capacity Induces Vascular Regeneration

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…This may also explain why elastic fiber assembly was only detected at late time points, at which the inflammatory environment had locally resolved in graft-free regions. The latter was recently reported by Duijvelshoff et al, who demonstrated a trend of mature elastic fiber regeneration in resorbable synthetic endovascular stents in pace with a reduction in macrophage presence [58]. Overall, the present findings regarding tissue formation and maturation suggest that scaffold resorption of in situ TEHVs should be relatively slow in order to allow for sufficient mature and functional tissue formation prior to full scaffold resorption.…”
Section: Discussionsupporting
confidence: 83%
“…This may also explain why elastic fiber assembly was only detected at late time points, at which the inflammatory environment had locally resolved in graft-free regions. The latter was recently reported by Duijvelshoff et al, who demonstrated a trend of mature elastic fiber regeneration in resorbable synthetic endovascular stents in pace with a reduction in macrophage presence [58]. Overall, the present findings regarding tissue formation and maturation suggest that scaffold resorption of in situ TEHVs should be relatively slow in order to allow for sufficient mature and functional tissue formation prior to full scaffold resorption.…”
Section: Discussionsupporting
confidence: 83%
“…Collagen I was abundantly distributed throughout the graft area (from the lumen to the adventitial layer), whereas collagen III expression was minimal. This may be the result of collagen III gradually shifting to collagen I during maturation, as seen in previous studies [15,20]. The wall thicknesses of native vessels and PCL/PDO grafts were 296 ± 10 and 618 ± 87 μm, respectively (p = 0.014; Fig.…”
Section: Results Of Immunohistological Stainingsupporting
confidence: 75%
“…CD68-positive cells (macrophages) were observed in the PCL/PDO grafts (Fig. 5 A, first panel), but were mainly localized in the graft remnants (tunica media and adventitia; yellow arrow) at low density, suggesting a minimal inflammatory response and active polymer resorption [ 20 ]. This result is consistent with previous findings of a considerable reduction in the number of CD68-positive cells at 4 months after implantation [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with recent findings by Duijvelshoff et al., who demonstrated a progressive regeneration of mature elastic fibers accompanied by a progressive decrease in macrophage presence in regenerative resorbable synthetic stents. [ 67 ] It is plausible that the early pro‐regenerative environment induced by IL‐4 contributes to a more favorable biochemical milieu for elastin accumulation, for example by limiting the secretion of elastase by pro‐inflammatory macrophages. [ 68 ]…”
Section: Discussionmentioning
confidence: 99%